The Romans - Chrisp, Peter (New York : Chelsea Juniors, 1994)
Presents the history and culture of the ancient Romans through an exploration of their artifacts, customs, beliefs, and daily routines.
Includes index.
5.5
3-6
Keywords: Rome -- Civilization -- Juvenile literature; Rome -- History -- Juvenile literature; Rome -- Civilization; Rome -- History; Rome -- Civilization; Rome -- History